Makna Laba Bagi Pelaku Bisnis Waralaba - Paranoan, Natalia (E-Jurnal Akuntansi, 2020)
The purpose of the study is to uncover the meaning of profits for businesses in the Big Bananas franchise. The phenomenon of franchise business in Indonesia is increasing which was previously dominated by foreign franchise businesses. The study uses qualitative research methods and one key person to uncover profits in the Big Banana franchise business. The results of this study indicate that so far earnings have only been reviewed based on mere earnings material. While profits are also about other contributions from the conduct of business enterprises, such as the highest level of responsibility for the natural environment around the business, including those related to company resources, leadership aspects, and competition aspects in the business world. Then, the meaning of profit for the owner is material profit, satisfaction profit, and social profit. Keywords: The Meaning Of Profit; Franchise; Material Profit; Satisfaction Profit; Social  Profit.